Decision Support System in Identification of Swallow's Nest Quality with Weighted Product Method: Sistem Pendukung Keputusan dalam Identifikasi Kualitas Sarang Burung Walet dengan Metode Weighted Product - ardialis; Sarjon Defit; Gunadi Widi Nurcahyo (SYSTEMATICS, 2021)
This Decision Support System is related to the Weighted Product method in considering the criteria and weights. The Weighted Product (WP) method is one of the methods used to complete the decision-making system by considering the criteria and weights. Decision-making on the quality of the best swallow's nest is that there are no determination criteria so that it does not provide a maximum decision. This method uses equations to connect attributes and only produces the largest value that will be selected as the best alternative. The use of the Weight Product method produces ranking results in accordance with calculations from the manual with both data showing an accuracy rate of 100%. These results are implemented into a website-based decision support system using PHP and Mysql programming in general the system built has been able to run and can produce ranking data well.